Impact of infection and labour on chemokine production by the placenta. (16th November 2010) - Rajesh, U; Macfarlane, T; Seager, AL; Jones, RH; Morgan, G; Thornton, CA
Abstract : Chemokine production by the placenta will regulate maternal leucocyte traffic in the intervillous space and, if secreted into the maternal circulation, maternal systemic immunity during pregnancy. Differences in the production of chemokines in association with intrauterine infection and/or labour might also have a role in the initiation and/or maintenance of labour at preterm and term. Explant cultures prepared from placentas collected after delivery at term were cultured with and without the prototypic inflammatory stimuli lipopolysaccharide (LPS; 10 ng/ml). Cell/tissue free culture supernatants were harvested and stored at −20°C until analysis for a range of chemokines using specific ELISAs. Of the panel of chemokines investigated, interleukin 8 (IL-8; CXCL8), IL-16, MCP-1 (monocyte chemotactic protein-1; CCL2) and ENA-78 (epithelial neutrophil activating peptide-78; CXCL3) were produced constitutively by placental explants and all but IL-16 were increased significantly by exposure to LPS. MIP-1α (macrophage inflammatory protein-1α; CCL3) was the only chemokine found to be not detectable in untreated samples but increased by LPS. The detectable chemokines are mainly chemoattractants for neutrophils and monocytes/macrophages so might have a role in innate immune defence of the placenta. These chemokines might be critical during the inflammatory response that characterises infection-associated preterm labour and normal labour at ter.